Extracting Groups of Individuals Using Custom-Clusterng - Esteva, Santiago; Figueras, Albert; Rosa, Josep Llluís De la (British Journal of Healthcare and Medical Research, 2022)
This paper presents a methodology to work on data or how to generate data to be analyzed by the Custom – Clustering algorithm proposed, to obtain groups of individuals or people's behavior on non-accounting opinions or interests, to be used to promote products, sales, advertising, etc. designed and oriented to a certain group of people who can be influenced by their interests. An example is presented discovering different patterns on a topic.